A buffer placement algorithm to overcome short-circuit power dissipation in mesh based clock distribution network - John Reuben; Mohammed Zackriya V.; Harish M. Kittur; Mohd Shoaib (Engineering Science and Technology, an International Journal, 2015)
In the recent past, Mesh-based clock distribution has received interest due to their tolerance to process variations in deep-sub micron technology. Mesh buffers are placed on the mesh to drive the large load capacitance of clock sinks and mesh wire capacitance. In this paper, we propose a buffer placement algorithm which can overcome the short circuit power dissipated in clock meshes. Our buffer placement algorithm uses clustering technique to judiciously place buffers such that short-circuit power is minimized while minimizing skew at the same time. This is verified by Monte carlo simulations incorporating process, voltage and systemic variations in NGSPICE.